PENGARUH BAURAN PROMOSI DAN LINGKUNGAN EKONOMI INTERNASIONAL TERHADAP KINERJA PEMASARAN EKSPOR KABUPATEN BADUNG - Agus Darmendra, Pande Made (Buletin Studi Ekonomi; VOL.19.NO.1.FEBRUARI 2014.(PP 1-117), 2016)
The effect promotional mix and internasional economic environment on export marketing performance in badung regency. Since the opening of the free market area in the world make the export marketing performance tends to decline in Badung regency. This is caused by a number of competitors who took part in the international markets, the development of  marketing mix variables and the international economic environment is considered influential in improving export performance. The purpose of this study was to determine the effect of partially and simultaneously between the marketing mix of international economic environment on the performance of export marketing in Badung regency. The results showed that there is a positive and significant effect between sales promotion (X) , the cost of printing brochures (X2) and per capita income in destination country (X) on export marketing performance in Badung (Y) . In addition , this study also shows that the independent variables promotional mix and influential international economic environment simultaneously on the export marketing performance in Badung, where the influence of the two independent variables of 69.7 percent, in other words 30.3 percent,  the performance of export marketing in Badung influenced by other variables that not included in the model.   Keywords: promotional mix, the international economic environment, the performance of the export marketing
Keywords: promotional mix, the international economic environment, the performance of the export marketing